The Impact of Sawmill Activities on Surface Water Quality in the Pessu Market Section of the Warri River (International Journal of Scientific Research and Management (IJSRM), 2023)
Solid waste serves as a substantial contributor to environmental contamination by introducing chemical substances into the environment in quantities that exceed acceptable limits. This study aims to ascertain the impact of sawmill activities on the surface water quality in the Pessu market section of the Warri River. Surface water samples were collected from 6 sampling points upstream and 6 sampling points downstream. Sampling and analysis of the surface water was done according to standard methods and procedures. The results of this study showed pH in the ranges of 6.5 – 6.91 and 6.81 – 7.09; turbidity ranged from 44.61- 90.89 NTU and 39.88 – 84.20 NTU; iron varied from 2.70 – 5.62 mg/L and 0.55 – 4.89 mg/L; Cadmium ranged from 0.54 – 0.60 mg/L and 0.55 – 0.74 mg/L for the upstream and downstream respectively. Water quality index result revealed that the water is not suitable for drinking. Turbidity, iron, and cadmium exceeded WHO standard limits for drinking water quality. The exceedances observed in this study are an indication that the sawmill activities may have a negative impact on the surface water quality in the study area. It is therefore recommended to carry out measures to mitigate these exceedances observed.